Sistematik Filogenetik Pseudomonas Strain Indigenous Pendegradasi Liniar Alkilbenzen Sulfonat - Suharjono, Suharjono; Sembiring, Langkah; Subagja, Yusup; Widayati, Wiwik E. (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
Linear Alkylbenzene Sulphonate (LAS) was the dominant pollutant in the river ecosystem. Indigenous strains of Pseudomonas in river ecosystem had highly potency to LAS degradation. This research was carried out to study relationship of indigenous strains of LAS degrading to Pseudomonas strains. Indigenous strains of bacteria of LAS degrading were characterized based on ARDRA (Amplified Ribosomal 16S rDNA Restriction Analysis) and 16S rDNA sequence. Result of the research shows that Pseudomonas strain J and R which LAS degrading from detergent polluted river ecosystem based on 16S rDNA sequence, isolate J has 98.37% similarity and it has relationship to P. pseudoalcaligenes LMG 1225T whereas isolate R has 84.86% similarity and related to P. stutzeri phen8.